Relação lisina digestível e energia metabolizável para leitões em fase pré-inicial de creche - da Trindade Neto, Messias Alves; Berto, Dirlei Antonio; de Albuquerque, Ricardo; Schammass, Eliana Aparecida (FapUNIFESP (SciELO), 2009)
It was studied the better digestible lysine:metabolizable energy (LIS:ME) and the effects of LIS and ME levels on performance and nitrogen retention in nursery piglets. In assay 1, 216 commercial piglets from 6.98 ± 1.16 kg (initial weight) at approximately 12 ± 0.62 kg were used and in the assay 2, 48 similar piglets at 9.31 ± 2.09 kg. The LIS levels were: 1.223, 1.302, 1.390 and 1.497% and ME: 3,510, 3,700 and 3,830 kcal/kg and were assigned in 3 × 4 factorial arrangement and distributed in randomized block design. On piglets performance there was interaction of LIS and ME for piglets weight gain and feed:gain. The response for LIS on weight gain was linear ascendant in diets with 3,510 kcal and 3,830 kcal ME. In feed:gain was observed quadratic effect of LIS in diets with 3,510 kcal and linear effect of LIS in diets with 3,830 kcal ME. The quadratic effect of LIS in 3,510 kcal ME diets indicated as a optimal level 1.44% of LIS or 4.16 g LIS/Mcal of ME. The positive linear response in feed: gain with LIS inclusion in 3,830 kcal EM diets indicated that piglets respond efficiently at amino acid increase when energy level is high. In metabolism study the ME increases suggest higher N retention, whereas the LIS increases suggest reduction in N retention or in ME Mcal:LIS % rate. The observed interaction in two assays however indicate that LIS:ME rate depend of energetic level and considered characteristics. In present conditions the change of LIS and ME indicate 1.44% or 4 g LIS/Mcal ME that correspond around 7.8 g LIS/day of ingestion. © 2009 Sociedade Brasileira de Zootecnia.
Digestible lysine: Metabolizable energy ratio for nursery piglets
Keywords: Digestible amino acid; Performance; Weaned